The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/agronomy12010178
|View full text |Cite
|
Sign up to set email alerts
|

Cup Plant (Silphium perfoliatum L.) Biomass as Substitute for Expanded Polystyrene in Bonded Leveling Compounds

Abstract: Biomass for non-food applications is considered as a substitute for petro-based materials such as expanded polystyrene (EPS). This research analyzes physical properties of an EPS containing commercial bonded leveling compound (BLC) which was substituted with cup plant (Silphium perfoliatum L.) biomass. Cup plant is a high-yielding biomass plant with several ecological benefits that is yet mainly used for biogas production. Furthermore, the high amount of parenchyma in senescent biomass with its EPS-like struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…The collected biomass of plants previously used in phytoremediation can be used in the production of building materials. The results indicate that late-harvested S. perfoliatum biomass could be a biobased substitute for EPS in bonded leveling compounds [221]. Another application of S. perfoliatum after phytoremediation may be the use of this biomass in the production of paper and packaging materials.…”
Section: Application For Soil Remediationmentioning
confidence: 92%
See 1 more Smart Citation
“…The collected biomass of plants previously used in phytoremediation can be used in the production of building materials. The results indicate that late-harvested S. perfoliatum biomass could be a biobased substitute for EPS in bonded leveling compounds [221]. Another application of S. perfoliatum after phytoremediation may be the use of this biomass in the production of paper and packaging materials.…”
Section: Application For Soil Remediationmentioning
confidence: 92%
“…In addition, the authors concluded that the cultivation of S. perfoliatum on contaminated soil precludes the use of the plants for fodder purposes [220]. Biomass for non-food applications is considered as a substitute for petro-based materials such as expanded polystyrene (EPS) [221]. The collected biomass of plants previously used in phytoremediation can be used in the production of building materials.…”
Section: Application For Soil Remediationmentioning
confidence: 99%
“…The data collection period of the field trial ranged from 26 May 2020 (34 days after sowing (DAS)) to 23 November 2021 (580 DAS), during which the development of the plant was documented weekly. Vegetative growth referred to the counting of nodes on the rosette as well as on the shoot.…”
Section: Data Collectionmentioning
confidence: 99%
“…Harvesting, as well as utilization, of any kind, in the first year of cultivation, should generally be avoided due to low yields and possible damage to the plants. A versatile usage of the second year biomass is possible [10,23,55]. Often, the time of harvest and the associated developmental stage or maturity is crucial for the use [19,23].…”
Section: Classification Of Phenotypic Traits and Usementioning
confidence: 99%
See 1 more Smart Citation